States and Local Legal Cultures in Medieval Islam: A comparative study of Akbar’s Mughal Rule and Sultan Agung’s Mataram in 16th and 17th Century - Noor Achmad; Nanang Nurcholis (Al-Jami'ah Research Centre, 2016)
This study seeks to expand the horizon of existing literatures on the dialectic of religion, legal culture and local dynamics by comparing two great Muslim rulers in two different parts of the world in the first Islamic millennium: Mughal Emperor Akbar and Mataram’s Sultan Agung. It specifically aims to analyze historical accounts on the dynamic relations between Islamic norms and local culture with corresponding results of distinctive ways of ruling by these two great rulers. While both rulers Akbar and Sultan Agung shared similar concerns in political imagination, their difference was particularly shown in the representation of religion in the courts’ political and legal culture, with the latter was heavily determined by different challenges they faced during their rule. This paper argues that a comparative overview of these two great figures, who ruled in different parts of the world and at rather successive periods, would be beneficial for the studies of religion-culture relations in flagging the variation and extent of manifestation of Islamic global norms in local legal cultures which heavily determined by their corresponding local dynamics. As a literary or library research, it uses eclectic, blended, with qualitative method in content analysis.[Studi ini berupaya memperluas horison literatur-literatur yang ada tentang dialektika agama, budaya hukum dan dinamika lokal dengan membandingkan dua penguasa besar Muslim di dua belahan dunia yang berbeda pada millennia Islam pertama yaitu Raja Akbar dari Dinasti Mughal dan Sultan Agung Kerajaan Mataram. Secara spesifik, studi ini bertujuan untuk menganalisa catatan-catatan historis relasi dinamis antara norma Islam dengan budaya lokal dengan hasil temuan yang menunjukkan cara berkuasa/memerintah yang berbeda diantara dua penguasa tersebut. Sementara keduanya (Akbar dan Agung) memiliki kemiripan dalam imajinasi politik, di sisi lain, perbedaan mereka ditunjukkan dalam hal representasi agama dalam budaya hukum dan politik terutama ditentukan oleh perbedaan tantangan yang mereka hadapi ketika mereka berkuasa. Studi ini membuktikan bahwa dengan membandingkan dua figur yang memerintah di belahan dunia yang berbeda pada masa yang berurutan, akan memberikan manfaaat terhadap studi relasi agama dan budaya dalam mewarnai variasi dan lingkup manifestasi norma-norma global Islam dalam budaya hukum lokal yang banyak ditentukan oleh dinamika lokal yang bersesuaian. Sebagai penelitian kepustakaan (literer), studi ini menggunakan pendekatan eklektik dengan metode kualitatif dalam analisis ini (content analysis)].